Public Values Leadership : Striving to Achieve Democratic Ideals - Bozeman, Barry; Crow, Michael M. (Book collections on Project MUSE., 2021)
"One of many objectives of leadership is upholding public values. But that objective may be quite different from other more conventional leadership objectives. This book discusses the requirements for effective leadership that promotes public values"--